Estudio del tratamiento periodístico en los diarios el comercio y el universo en torno a “la marcha de las putas - Pineda Sandoval, Karina Alene (2016)
This research analyzes the journalistic treatment that El Comercio and El Universo newspapers give called La Marcha de las Putas, which since 2012 is held annually in the city of Quito. Criteria and authors who have previously analyzed this issue from other perspectives was taken as reference. The work was based on the approach communicator Edwin Flores that addresses the issue of journalistic discourse regarding the display of La Marcha de las Putas within historical areas in that city, as well as the theoretical support of Umberto Eco when dealing with the subject of "possible worlds" that are real worlds, worlds of reference and possible worlds….